MANAJEMEN PENDEKATAN PEMBELAJARAN - Suryapermana, Nana (Tarbawi, 2017)
To create a good and perfect learning power is not as easy as turning your palms, or not as difficult as turning your foot. This needs to be studied and reflected in the nature of our minds, so that the learning process does not sink into the abyss of error, which will only destroy the students' learning outcomes, which makes the students do not know the direction, where the step of this learning objective goes. To generate self-confidence, passion and the spirit of student learning, there needs to be a concept of "Approach" of learning that is built and created by the teacher. In our minds and minds, there must be a grain of questions about what that "approach" is. Here we try to philosophize without eliminating and without burning the results of thoughts and rekayaa others. What is meant Approach in this learning is a learning process created and mastered by teachers in teaching and learning process. Or how the teacher approaches the student learning. So it is with the expression in Joni's mind (1980: 15) that the meaning of "approach" is a general way of looking at the problem and object of study, so that the impact is like someone using certain glasses in view of nature. Green glasses will make the world namapk greenish, as well as using brown glasses, the world feels brown and so on. Next let's try to listen to listen and analyze, then we input into our natural thoughts about the meaning of the approach presented Sanjaya (2006: 36), "The approach can be interpreted as a point of departure or our point of view of the learning process. From the above perspective, surely our minds and our souls must fall down and sink into the minds of Masitoh and Goddess (2009: 38) which offer a learning approach and they say: the learning approach is a way of looking at and understanding the learning situation. There is another saying to the bottom of another fish, another grasshopper. Likewise in terms of learning approaches, the more people think, the more piling up, the smarter the person, the more science that is inspired by the results of reflection and experience. Therefore, the mind of W. Gulo, on the understanding of the learning approach, which is repackaged by Siregar and Nara (2010: 75) explains that the learning approach is a view in seeking the way students interact with their environment. Keywords: Management, Learning Approach.